Modulation of reaction kinetics for the tuneable synthesis of gold nanoparticles and quantum clusters: application of gold quantum clusters as ``turn-off'' sensing probe for Sn4+ ions - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (ChemPlusChem, 2014)
The syntheses of gold nanoparticles (Au NPs) and gold quantum clusters (Au QCs) that employ cefadroxil (CFX; an antibiotic) as both reducing and capping agents are reported. The HAuCl4/CFX concentration, temperature, and pH are crucial factors in the modulation of the nucleation and growth kinetics of the reaction, and consequently, in guiding the size and morphology of as-synthesized Au NPs. Interesting results are observed if the reaction is performed under different pH conditions. TEM analysis of the Au NPs synthesized at pH 6 shows an average particle size of approximately 2 nm along with a relatively smaller population of bigger NPs (up to 6 nm). The Au QCs were isolated by high-speed centrifugation and showed fluorescence at lambda approximate to 460 nm. Furthermore, the as-synthesized Au QCs were applied as sensor for Sn4+ ions on the basis of an aggregation-induced fluorescence quenching mechanism. These Au QCs offer acceptable sensitivity, high selectivity, and a limit of detection of approximately 10 mm for the determination of Sn4+ ions.